Dehumanization within the Prophetic Ethical Framework in the Novel 'Hidup Ini Keras Maka Gebuklah (Trilogi Ipung)' by Prie GS - Arbi, Muhammad; Haryati, Nas; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One manifestation of dehumanization within the framework of prophetic ethics is the existence of the 'man-machine.' Humans lose their humanity and experience spiritual alienation. This phenomenon is found in the novel Hidup Ini Keras Maka Gebuklah (Trilogi Ipung) by Prie GS. The purpose of this research is to describe the dehumanization depicted through the characteristics of the 'man-machine' in the novel Hidup Ini Keras Maka Gebuklah (Trilogi Ipung) by Prie GS. The approach used in this study is the sociological literary approach. The heuristic method is employed to gather data, which consists of excerpts from the novel Hidup Ini Keras Maka Gebuklah (Trilogi Ipung). Data analysis in this research employs the hermeneutic method. The findings of this research include characteristics of dehumanization in the form of the 'man-machine' in the novel, which involve the presence of machinery and techniques in all fields, human activities based solely on stimulus and response, and the presence of enlightenment, awareness, guidance, or a 'God spot'.